Comparative transcriptome analysis of genes involved in paradormant bud release response in ‘Summer Black’ grape - Fan, Shaogang; Luo, Feixiong; Wang, Meijun; Xu, Yanshuai; Chen, Wenting; Yang, Guoshun (Frontiers in Plant Science, 2023)
Grapevines possess a hierarchy of buds, and the fruitful winter bud forms the foundation of the two-crop-a-year cultivation system, yielding biannual harvests.Throughout its developmental stages, the winter bud sequentially undergoes paradormancy, endodormancy, and ecodormancy to ensure survival in challenging environmental conditions. Releasing the endodormancy of winter bud results in the first crop yield, while breaking the paradormancy of winter bud allows for the second crop harvest. Hydrogen cyanamide serves as an agent to break endodormancy, which counteracting the inhibitory effects of ABA, while H2O2 and ethylene function as 带格式的: 缩进: 首行缩进: 0.99 厘米 设置了格式: 下标 设置了格式: 下标 VvPIN3 and VvTIR1. Short pruning induced the generation of reactive oxygen species, which further amplified through the MAPK cascade, thereby activating the expression of genes associated with the glutathione peroxidase cycle and the ascorbateglutathione cycle (VvGPX, VvAPX, VvGST), starch and glucose metabolism (VvBMY).Hydrogen cyanamide treatment directly disrupted mitochondrial function, resulting in ROS production and a prolonged induction efficacy of the growth hormone signaling pathway. The application of hydrogen cyanamide increased the sprouting rate and improved uniformity in the hydrogen cyanamide-treated group, meeting the stringent management requirements for timely and effective in second crop cultivation.